A long period grating optical fiber sensor with nano-assembled porphyrin layers for detecting ammonia gas - Wang, Tao; Yasukochi, Wataru; Korposh, Sergiy; James, Stephen W.; Tatam, Ralph P.; Lee, Seung-Woo (Elsevier, 2016)
In this study, the ability of a long period grating (LPG) optical fiber sensor coated with a multilayer film of poly(diallyldimethyammonium chloride) (PDDA) and tetrakis(4-sulfophenyl)porphine (TSPP) to detect ammonia gas was demonstrated. The nano-assembled thin film was prepared using a layer-by-layer deposition technique. This combination of an LPG and TSPP could allow highly sensitive optical sensors that specifically bind ammonia to be fabricated. An LPG with a period of 100 μm and a PDDA/TSPP coating produced by depositing fifteen layers afforded a limit of detection of 0.67 ppm for ammonia gas. TSPP molecules in the film acted as ammonia receptors because the TSPP morphologically changed from J- or H-aggregates to free base monomers when it was deprotonated by being exposed to ammonia. Interestingly, HCl vapor could be used to increase the relative amount of J-aggregation in the TSPP and to restore the sensor response. The reversibility of the morphological change in the TSPP allowed reversible changes to occur in the properties of the coating, including the refractive index, film thickness and density, and electrostatic interactions; these influenced the transmission spectrum of the LPG.